Biomechanical Response of Lung Epithelial Cells to Iron Oxide and Titanium Dioxide Nanoparticles - Oliveira, Vinícius Rosa; Uriarte, Juan José; Falcones, Bryan; Jorba, Ignasi; Zin, Walter Araujo; Farré, Ramon; Navajas, Daniel; Almendros, Isaac (Frontiers in Physiology, 2019)
There is increasing evidence that lungs can be damaged by inhalation of nanoparticles (NPs) at environmental and occupational settings. Recent findings have associated the exposure to iron oxide (Fe2O3) and titanium dioxide (TiO2) -NPs widely used in biomedical and clinical research- with pulmonary oxidative stress and inflammation. Although changes on cellular mechanics could contribute to pulmonary inflammation, there is no information regarding the effects of Fe2O3 and TiO2 on alveolar epithelial cell biomechanics. The aim was to investigate the NPs-induced biomechanical effects in terms of cell stiffness and traction forces exerted by human alveolar epithelial cells. Cell Young’s modulus (E) measured by atomic force microscopy in alveolar epithelial cells significantly decreased after exposure to Fe2O3 and TiO2 (~28% and ~25%, respectively) compared to control conditions. Moreover, both NPs induced a similar reduction in the traction forces exerted by the alveolar epithelial cells in comparison to the control conditions. Accordingly, immunofluorescence images revealed a reduction of actomyosin stress fibers in response to the exposure to NPs. However, no inflammatory response was detected. In conclusion, an acute exposure of epithelial pulmonary cells to Fe2O3 and TiO2 NPs, which was mild since it was non-cytotoxic and did not induce inflammation, modified cell biomechanical properties which could be translated into damage of the epithelial barrier integrity, suggesting that mild environmental inhalation of Fe2O3 and TiO2 NPs could not be innocuous.